USE OF DRONE FOR EARLY DETECTION MEANS LAND AND FOREST FIRE - Petrisly Perkasa; Yusuf Aguswan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
In the last few years Palangka Raya City was hit by many points of forest and land fires (Karhutla) that have sprung up intentionally or not sporadically which resulted in smoke and an unpleasant atmosphere which would trigger material losses and of course the health of the surrounding community that inhaled the smoke left over from forest fires and the land. This condition also results in health, economic, social and environmental losses which will certainly hamper the pace of development and the ongoing development of the City of Palangka Raya. The main objective of this research is the use of drones to detect and community preparedness for forest and land fire disasters in areas that have potential for forest and land fires.